Petrography and Depositional Evolution of Zubair Succession in Rumaila and West-Qurna Oilfields, Southern Iraq - Ghareb, Risan Hamod; Alawsi, Munther D.; Al-Zaidy, Aiad Ali Hussien (Iraqi Journal of Science, 2025)
This study encompasses the petrography, lithofacies analysis, and depositional development of the Zubair Formation in four boreholes (Ru-X1, R-X2, WQ-X1, WQ-X2) located within the Rumaila and West-Qurna oil fields. The Zubair Formation depositional basin was located in the Mesopotamian Foredeep during the Barremian age. Zubair succession mainly consists of sandstone, specifically quartz arenite (or orthoquartzite), with about 93% or more quartz grains. Rocks containing over 20% lithic-fragments and minor feldspars are classified as lithic-arenites, and those containing over 30% clay content along with minor lithic fragments are classified as greywackes. Five main lithofacies have been identified within two dominant rock groups across two major successions. The first group, sand-dominated rocks, includes well-sorted, sub-rounded quartz arenite lithofacies; poorly sorted, sub-angular quartz arenite lithofacies; and poorly sorted graywacke lithofacies. The second group, clay-dominated rocks, consists of sandy claystone and shale lithofacies. Three facies associations are identified in the studied succession: delta plain, shore-face, and back-shore. These associations were deposited over three cycles, dividing the Zubair succession into three units. The lower unit of the Zubair Formation is mainly composed of shale, with thin sandstone beds and lenses separating it into two parts. In the northern part of the study area, the upper part consists of sandstones, while the lower rock unit is dominated by shaly beds. The middle unit of the Zubair Formation is the thickest and features alternating shale-dominated and sand-dominated beds, forming three depositional cycles, most prominent in the southern part of the study area (Rumaila oilfield), whereas the northern part (West-Qurna) has two cycles. The upper unit of the Zubair Formation is mainly composed of well-sorted, sub-rounded quartz arenite lithofacies, indicating deposition in a shoreface environment and marking a sea-level rise in the Rumaila oilfield. In the West-Qurna oilfield, this unit is represented by delta plain and backshore facies associations. This cycle marks the conclusion of Zubair deposition during the transgressive stage, transitioning into the Shuaiba Formation.